Governing the “Golden Age of Infrastructure”: Assessing Transparency Innovations in Philippine Infrastructure Development - Mendoza, Ronald U (Archīum Ateneo, 2020)
Amidst rising infrastructure investment across the Asia‐Pacific, glaring accountability deficits have raised questions about governments’ capacity to contain corruption in infrastructure development in the region. Recent developments in the Philippines, however, indicate the presence of challenges related to the ability of digitally enhanced transparency measures to bridge such accountability deficits. This article presents the shifting emphasis in transparency and accountability reforms related to Philippine infrastructure development beginning from the 1990s and assesses transparency innovations under the Duterte administration. While milestone measures such as the establishment of an electronic freedom of information (eFOI) platform have provided convenient access to public information, major hurdles remain in obtaining critical documents concerning infrastructure projects. As borne out in an exercise to request the feasibility studies of 48 flagship infrastructure projects, access to information is still obstructed by factors ranging from technical constraints, uneven service delivery, coordination failures, as well as active legal restrictions against the public’s right to know.